ChemInform Abstract: RhIII‐Catalyzed C—H Activation with Pyridotriazoles: Direct Access to Fluorophores for Metal‐Ion Detection. Issue 3 (29th December 2015) - Kim, Ju Hyun; Gensch, Tobias; Zhao, Dongbing; Stegemann, Linda; Strassert, Cristian A.; Glorius, Frank
Abstract: Substituted pyridines and isoquinoline (VI) are used as coupling partners under conditions A).